INVENTORY OF BIRDS PRESENT OF THE “LAGUNA PUNRUN”, DEPARTMENT PASCO, PERÚ - Cabanillas-Trujillo, Elizabeth F. (2021)
Bird inventories make it possible to quickly and accurately identify the ecological characteristics and the degree of conservation of most of the species that constitute the group of terrestrial vertebrates with the greatest richness and abundance worldwide and of great sensitivity, which makes them excellent indicators of environmental quality. This research was developed in an altitudinal range between 4306 and 4730 masl, encompassing habitats such as Andean pajonal, Lagoons or Cochas, Bofedales and Areas of scarce vegetation being the high Andean areas a source of refuge and food for different species. From the information obtained in the field, by reviewing the ornithofauna databases and consulting specialists, 10 orders were identified, with the Passeriformes group being the most dominant, 16 families representing 54% of the population among they Furnariidae (17%), Thraupidae (13%), Anatidae (8%), Falconidae (8%) and Threskiornithidae (8%). and 24 species present in the study area within which Geositta saxicolina (Taczanowski, 1875) as an endemic species. According to IUCN (International Union for Conservation of Nature) one species near threatened, and 21 species (Least Concern). In CITES (Convention on International Trade in Endangered Species) four species in appendix II and two species were registered in the national category near threatened and one in vulnerable condition.